The mediation effect of peer relation and positive emotion between campus sports atmosphere and teenagers’ subjective well-being - Cheng, Weibo; Jiao, Long (Frontiers in Psychology, 2024)
BackgroundThe healthy growth of young people affects the future of every country and nation. Their physical and psychological health problems have long been the focal point of every country. The purpose of this study is to investigate the influence of campus sports atmosphere on the teenagers’ subjective well-being.MethodThis study was conducted among 10 to 15 year old teenagers in Jinan City, by means of campus sports atmosphere, peer relation, positive emotion and subjective well-being. The original data is exported in Excel format from Wenjuanxing Platform, and SPSS 26.0 is used to perform descriptive statistics, reliability, and correlation analysis.ResultsThe correlation coefficient of campus sports atmosphere, peer relations, positive emotion, and teenagers’ subjective well-being is significant; the results showed that the campus sports atmosphere had a positive predictive effect on the peer relationship (β = 0.699, t = 17.729, p < 0.01), and positive emotion (β = 0.38, t = 16.783, p < 0.01). Campus sports atmosphere can predict the teenagers’ subjective well-being positively (β = 0.289, t = 14.723, p < 0.01); The relationship between peer relations and positive emotion can predict the teenagers’ subjective well-being positively (β = 0.292, t = 15.24, p < 0.01; β = 0.355, t = 18.669, p < 0.01); Through Bootstrap Testing, we find that the campus sports atmosphere has a significant positive influence on the teenagers’ subjective well-being, which is 0.4969; The influence of the relationship between the campus sports atmosphere and the teenagers’ subjective well-being was significant, and the total indirect influence was 0.4352.ConclusionThe campus sports atmosphere not only influences teenagers’ subjective well-being directly, but also improves their well-being by the mediation of peer relations and positive emotion.